2016
DOI: 10.1111/jfq.12219
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Volatile Compounds of Foam Mat Dried Corn Flour

Abstract: Foam mat drying is good in dehydrating liquid foods in a short time. The porous structure of foam material contributes to high drying rate and consequently shorter dehydration time. Corn flour was produced using foam mat drying and its quality was compared to freeze‐dried corn flour. Different concentrations of egg albumen (10, 15 and 20%) and whipping time (5, 10 and 15 min) were used. Foaming characteristics of corn slurry produced were investigated. Corn slurry produced with 20% egg albumen and 15 min whipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Kandasamy et al (2012) reported that the biochemical compositions in the foamed dried papaya powder were significantly higher than those of the non-foamed dried papaya powder. A similar result was also reported by Teoh et al (2016) that the protein content in foam mat dried corn flour was higher than the protein content in non-foamed dried corn flour.…”
Section: Chemical Properties Of Dried Pasta Saucesupporting
confidence: 89%
“…Kandasamy et al (2012) reported that the biochemical compositions in the foamed dried papaya powder were significantly higher than those of the non-foamed dried papaya powder. A similar result was also reported by Teoh et al (2016) that the protein content in foam mat dried corn flour was higher than the protein content in non-foamed dried corn flour.…”
Section: Chemical Properties Of Dried Pasta Saucesupporting
confidence: 89%
“…the similar observation as be doing by Kavitha and Parimalavalli (), who has observed that the roasted treatment significantly ( p ˂ 0.05) affected the lipids content of cereals compared to raw material. Concerning corn flour, the fats content are greater than those of Kavitha and Parimalavalli () and Teoh, Lasekani, and Azeez () on foam dried corn flour (3.83%). This can be explained by the variety of plant, the climate condition of the locality where they have growth, the treatment applied to these flours.…”
Section: Resultsmentioning
confidence: 83%
“…(2016) also found no significant difference between the protein content of dry yacon juice dried in foam mat at temperatures of 50, 60, and 70°C. On the contrary, Teoh, Lasekan, and Azeez (2016) found that the protein content of corn flour decreased with increasing temperature during foam mat drying.…”
Section: Resultsmentioning
confidence: 97%